Herramientas multimedia para fortalecer la competencia digital en los docentes (Dossier: Comunicación, educación y pedagogías mediáticas) - Díaz Espinel, Emilio Jhon (2025)
The research addresses the use of multimedia tools as a strategy to strengthen the digital competencies of teachers, in a context where technological progress demands significant adaptations in education. Faced with the problem of limited digital training of teachers, the objective was to develop a training strategy based on multimedia tools that contribute to the strengthening of digital competence in teachers; having as specific objectives: to identify tools used, evaluate digital competencies and propose strategies for improvement. The study, with a quantitative approach, used surveys applied to 177 teachers, whose data were statistically analyzed. The results of the theoretical background show that tools such as Canva and PowerPoint are widely accepted. The statistical analysis indicated a high positive correlation (ρ=0.942ρ=0.942ρ=0.942ρ=0.942) between the use of multimedia tools and the strengthening of digital competencies, highlighting that advanced areas, such as audiovisual editing, require greater attention. The positive impact of multimedia tools in teaching is highlighted, but their implementation has been facing technical and formative challenges, so this work presents a contribution to the training of teachers’ competence using the benefits of multimedia tools. It concludes on the importance of developing permanent training programs, improving the technological infrastructure and promoting institutional policies that facilitate the effective integration of these tools, thus guaranteeing learning adapted to the demands of the 21st century.